An Economical and Practical Synthesis of rac‐(Z)‐β‐Santalol: Application of a Scriabine‐Inspired Reaction to Alkenes Results in the One‐Step Preparation of a Key Intermediate1. Issue 34 (29th October 2014) - Birkbeck, Anthony A.; Marquet, Xavier; Millet, Pascal; Pamingle, Hervé
Abstract: An economical and practical synthesis of rac ‐( Z )‐β‐santalol was accomplished. The key coupling step is based on a Scriabine‐inspired reaction of a dienyl diacetate substrate and an alkene. The total synthesis was achieved in five steps (longest linear sequence) in 19 % overall yield from cyclopentadiene. Abstract : An economical and scalable synthesis of rac ‐( Z )‐β‐santalol is accomplished. The key coupling step is based on a Scriabine‐inspired reaction of a dienyl diacetate substrate and an alkene. The total synthesis is achieved in five steps (longest linear sequence) in 19 % overall yield from cyclopentadiene; Cp* = C5 Me5, cod = 1, 5‐cyclooctadiene, Tf = trifluoromethylsulfonyl.